PENGARUH AUDIT INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN INTERN BIAYA PRODUKSI - Aristanti Widyaningsih (STIE Pelita Nusantara Semarang, 2010)
This research is aimed to know the influences of internal auditing toward effectiveness of internal control of cost production of Satuan Pengawasan Intern (SPI) PT Dirgantara Indonesia (Persero) Bandung. The method of this research use the survey method, which is the information and data are getting from the respondent by using inquiry. The respondents are staffs of Satuan Pengawasan Intern (SPI) PT Dirgantara Indonesia (Persero) Bandung. Sampling technique that used for this research is non probability sampling with the satisfied sampling technique. The based of this technique is taking from the sample source that come from entire populations of the research that is as much as 20 person, so this research is also called the population research.There are two variables, internal auditing as independent variable (X) and the effectiveness of internal control of cost production as dependent variable (Y). The data analysis by checking it through the average (mean) calculation, meanwhile, for testing the hypothesis is used Product Moment correlation and to detect how much variable X can give support towards variable Y by used determination coefficient.From the testing of the hypothesis is found there is a high influences of internal auditing toward effectiveness of cost production internal control, the value is 51%. This value means that variable X influencing the variable Y 51% and the remainder 49% is influenced by another factors which not elaborated in this research